The Association between Frailty Status, Multimorbidity, and Patient Demographics, and Changes in Primary Care Since the COVID-19 Pandemic: A Retrospective Cohort Study - Fikree, Shireen (My University, 2022)
Purpose: With the start of the SARS-COV-2 pandemic in March 2020, Canadian primary care practices temporarily shifted from in-person to virtual care. The purpose of this thesis was to understand whether the pandemic impacted the primary care management of older adults with varying levels of frailty and multimorbidity in terms of care modality, volume of encounters, and visits for anxiety/depression. It also aimed to identify which patients comparatively experienced greater reductions in frequencies of routine preventive care and monitoring activities. Methods: A research database from a sub-set of MUSIC family practice for patients ≥ 65 years of age (n=1813) was employed. Patient demographics, clinician-assessed frailty status, encounters, and chronic disease management information were retrieved. Changes from 14 months pre to 14 months since (peri) the pandemic were described and associations between patient characteristics and the extent of changes in outcomes from pre- to peri-pandemic were analyzed using regression models. Results: The mean age was 74 years, with a mean of 2.5 chronic conditions (26% hypertension, 14% diabetes). 2.1% of patients experienced high frailty levels. The mean number of encounters increased peri-pandemic overall (peri: 10.4 (SD 11.1) vs. pre: 7.1 (SD 5.5)) and for anxiety/depression, with most visits becoming virtual. Increasing numbers of overall visits were significantly associated with female sex, increasing frailty level, and having 4+ conditions. While the frequency of routine preventive and monitoring activities related to chronic conditions decreased, the mean values (e.g., lab results) did not considerably change. In the adjusted models, generally older patients, with increasing levels of frailty, and numbers of conditions tended to receive more care, however most associations were not statistically significant. Conclusion: Overall encounters and visits related to anxiety/depression increased peri-pandemic. Despite concerns about pandemic-related care disruptions, common elements of primary care among higher risk older patients were not notably impacted.
Changes In Primary Care Of Older Adults Since COVID-19
Keywords: Frailty; Multimorbidity; Chronic Disease; Socioeconomic Status; Primary Care; COVID-19; Virtual Care; Telemedicine